2022
DOI: 10.1001/jamaneurol.2022.1269
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Prenatal Exposure to Antiseizure Medication With Risk of Autism and Intellectual Disability

Abstract: IMPORTANCEWomen with epilepsy frequently need antiseizure medication (ASM) to prevent seizures in pregnancy. Risk of neurodevelopmental disorders after prenatal exposure to AMSs is uncertain.OBJECTIVE To determine whether children exposed prenatally to ASMs in monotherapy and duotherapy have increased risk of neurodevelopmental disorders. DESIGN, SETTING, AND PARTICIPANTSThe Nordic register-based study of antiepileptic drugs in pregnancy (SCAN-AED) is a population-based cohort study using health register and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 129 publications
(154 citation statements)
references
References 46 publications
(118 reference statements)
7
125
1
1
Order By: Relevance
“…However, the con dence intervals of the second and third trimester exposures varies widely, probably due to the smaller sample size used (67 children), and so was not powered enough to detect a meaningful association. The ndings of Christensen was supported by Bjørk et al [15] who found that exposure to valproate during the second and third trimesters without exposure during the rst trimester was still associated with an increased risk of ASD with a HR of 1.94 (1.04-3.60). Bjørk et al [18], and Wood et al [13] studied the usefulness of folic acid supplements in the rst trimester in preventing ASD, so the supposed increase in the risk of ASD in rsttrimester exposure to ASM is extrapolated from the fact that women who did not take folic acid early in pregnancy had increased risks of producing autistic children.…”
Section: Risk Of Asd According To Trimester Of Exposure To Asmmentioning
confidence: 81%
See 4 more Smart Citations
“…However, the con dence intervals of the second and third trimester exposures varies widely, probably due to the smaller sample size used (67 children), and so was not powered enough to detect a meaningful association. The ndings of Christensen was supported by Bjørk et al [15] who found that exposure to valproate during the second and third trimesters without exposure during the rst trimester was still associated with an increased risk of ASD with a HR of 1.94 (1.04-3.60). Bjørk et al [18], and Wood et al [13] studied the usefulness of folic acid supplements in the rst trimester in preventing ASD, so the supposed increase in the risk of ASD in rsttrimester exposure to ASM is extrapolated from the fact that women who did not take folic acid early in pregnancy had increased risks of producing autistic children.…”
Section: Risk Of Asd According To Trimester Of Exposure To Asmmentioning
confidence: 81%
“…After screening the title/abstracts and full-text information, 196 and 27 studies were excluded, respectively. Finally, 10 studies that met the inclusion criteria were included [9][10][11][12][13][14][15][18][19][20] .The study selection ow chart is shown in Fig. 1.…”
Section: Study Identi Cation and Selectionmentioning
confidence: 99%
See 3 more Smart Citations